PEMPROFILAN PELAKU TERORIS ANAK - Saraswati Saraswati; Elsafira Maghfiroti Resyanta (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2020)
The background of this study is to examine the profile of child terrorist and the motivation behind the crime of terrorism in children by using child development theory and sosial ecology theory. This research is a qualitative study using a phenomenology approach. The phenomenology approach aims to describe the meaning of the life experience of a terrorist child so that the level of belief or paradigm of the terrorist child changes, so to learn and understand it must be based on the point of view of a terrorist child as a subject who directly experiences the incident. The subject of this research is a child who commits a terrorist crime. Data collection techniques by conducting deep interviews, observation and documentation study. This research was conducted at the Juvenile Penitentiary Class I Tangerang (LPKA). The results of this study indicate that the profile picture of a child terrorist can be assessed based on the child's speaking style, behavior, motivation, beliefs, and experiences in the past. The main factor for a child committing a terrorist crime comes from the lack of figures and supervision from parents in their teens so that children look for other figures to be used as examples.